Assessment of Information Literacy Courses for PhD Students - Repanovici, Angela; Koukourakis, Manolis (Qualitative and Quantitative Methods in Libraries, 2017)
Information literacy courses for PhD students have to be designed with new requirement of information technology.   One survey was developed to doctoral school at Transilvania university of Brasov and PhD students of University Library of Crete. It was focused on information literacy  and needs of PhD students, current practices and strategies on: Finding resources for your literature review and beyond,  Good academic practice when writing your thesis,  The databases that help you choose where to publish, Citation searching, , Measuring and Improving your research impact with bibliometrics. It will be present survey results, comparison between the two institutions and one model of curricula for information literacy course for doctoral students.